Distribution of Hemoglobin A1c (HbA1c) and Its Associated Factors in Adults - Irmayanti Irmayanti; Arta Farmawati; Martalena Br Purba (PERSATUAN AHLI GIZI INDONESIA, 2019)
HbA1c is a parameter that may be used in predicting and diagnosing diabetes. Since diabetes is predicted to increase in Indonesia, it is necessary to understand the distribution and associated factors of HbA1c in the general Indonesian population. However, those data are still limited. This study aims to determine the distribution of HbA1c and its associated factors in Indonesian adults. We conducted a cross-sectional study analyzing data from Indonesia Family Life Survey (IFLS) 2014-2015. HbA1c was analyzed using dried blood spot (DBS) specimen with Bio-Rad D10 HPLC. We performed Student’s t test and ANOVA to show the results of the bivariate analyses and multiple linear regression to determine the association between variables. The study included 4.101 subjects (20-59 years) without diabetes and provided an overview of the distribution of HbA1c levels based on socio-demographic factors and smoking behavior described in percentiles. The mean of HbA1c was 5.35% with a standard error of 0.01. The threshold value of HbA1c for prediabetes (5.7%) corresponded approximately to the 75th percentile. Although there were differences in HbA1c distribution, socio-demographic factors such as education levels, employment, and settlement region as well as smoking were not independently associated with HbA1c levels in Indonesian adults. Furthermore, age and sex were associated with HbA1c.